A very beautiful writing. The politicity of metaphor (2020)
This article addresses a case study of the novel Una muchacha muy bella (2013) by Argentine writer Julián López, it focuses on the analysis of its metaphors, especially those that, through an extremely poetic treatment of language, evoke state terrorism, social context within which the narration takes place. While we are faced with rhetorical figures that work by relating two words by similarity, their use reveals not only the author's writing decisions and aesthetic preferences, but also the need for their use to account for the unspeakable and ineffable nature of what they narrate; their political potentiality is contained and suggested in metaphor. With the general objective of putting the literary production of an era to dialogue with the social and political context in which it arises, in the first place, we enroll the novel in the universe of the narratives of the second generation of post-dictatorship that emerged during the Kirchnerist period. Then we focus on the metaphors that are enunciated in the first part of the novel by the voice of the child narrator, specifically those that refer to the threatening climate of the repressive moment. Finally, we point out the tension that this novel implies in the series of stories pertaining to ""familism"", proposing to think about the writing practice in its political dimension, that is, in its ability to enable other voices and other ways of saying collective memory.